2021
DOI: 10.1371/journal.pone.0260244
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 affected the food behavior of different age groups in Chinese households

Abstract: The COVID-19 pandemic brought profound changes to all corners of society and affected people in every aspect of their lives. This survey-based study investigated how household food related matters such as food sourcing and consumption behaviors of 2,126 Chinese consumers in different age groups changed approximately two months into the COVID-19 quarantine. A new food sourcing mechanism, community-based online group grocery-ordering (CoGGO), was widely adopted by households, particularly among the youngest grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In the studies, different associations were drawn between demographic variables (e.g., gender, age, provenance, income, number of household members, education) and food waste production, showing that these variables define the basic circumstances that drive consumer choice. In particular, gender and age (Berjan et al, 2021 ; Brizi & Biraglia, 2021 ; Burlea-Schiopoui et al, 2021 ; Chen et al, 2021 ; Cosgrove et al, 2021 ; Principato et al, 2020 ; Qian et al, 2020 ; Vidal-Mones et al, 2021 ), level of education (Jribi et al, 2020 ), income and relative change in income (Heikal Ismail et al, 2020 ; Jribi et al, 2020 ; Rodgers et al, 2021 ; Vargas-Lopez et al, 2021 ), employment (Scacchi et al, 2021 ; Scharadin et al, 2021 ), and number of household members (Everitt et al, 2021 ; Pappalardo et al, 2020 ; Qian et al, 2020 ; Vidal-Mones et al, 2021 ) were the most debated factors, and shown to be significantly associated with food waste during the pandemic (Amicarelli et al, 2021 ; Muresan et al, 2022 ). Most studies highlighted the lower volume of food waste generated by women, older people, and people with low income.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In the studies, different associations were drawn between demographic variables (e.g., gender, age, provenance, income, number of household members, education) and food waste production, showing that these variables define the basic circumstances that drive consumer choice. In particular, gender and age (Berjan et al, 2021 ; Brizi & Biraglia, 2021 ; Burlea-Schiopoui et al, 2021 ; Chen et al, 2021 ; Cosgrove et al, 2021 ; Principato et al, 2020 ; Qian et al, 2020 ; Vidal-Mones et al, 2021 ), level of education (Jribi et al, 2020 ), income and relative change in income (Heikal Ismail et al, 2020 ; Jribi et al, 2020 ; Rodgers et al, 2021 ; Vargas-Lopez et al, 2021 ), employment (Scacchi et al, 2021 ; Scharadin et al, 2021 ), and number of household members (Everitt et al, 2021 ; Pappalardo et al, 2020 ; Qian et al, 2020 ; Vidal-Mones et al, 2021 ) were the most debated factors, and shown to be significantly associated with food waste during the pandemic (Amicarelli et al, 2021 ; Muresan et al, 2022 ). Most studies highlighted the lower volume of food waste generated by women, older people, and people with low income.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Cosgrove et al ( 2021 ), while confirming these results, suggested that food waste produced by younger generations may relate to fewer responsibilities in food preparation and procurement, relative to older generations, who may have also experienced greater economic challenges during the pandemic. Chen et al ( 2021 ) and Berjan et al ( 2021 ) highlighted the greater responsibility of older people regarding food waste. In parallel, Chen et al ( 2021 ) noted a sharp increase in online food purchases, fewer trips to the grocery store, and the purchase of extra food to compensate for fewer trips; while Berjan et al ( 2021 ) reported better food practices, such as meal planning and the purchase of lesser quantities of food.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations